1994
DOI: 10.1073/pnas.91.7.2517
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of rat liver 3 alpha-hydroxysteroid/dihydrodiol dehydrogenase: a member of the aldo-keto reductase superfamily.

Abstract: The 3.0-resolution x-ray structure of rat liver 3a-hydroxysteroid dehydrogenase/dihydrodiol dehydrogenase (3a-HSD, EC 1.1.1.50) was determined by molecular replacement using human placental aldose reductase as the search model. The protein folds into an a/ or triose-phosphate Isomerase barrel and lacks a coI Rossmann fold for bnding pyridine nucleotide. The structure contains a concentration of hydrophobic amino adds that lie in a cavity near the top ofthe barrel and that are presumed to be involved in binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 36 publications
(33 reference statements)
4
93
1
Order By: Relevance
“…Twelve amino acid residues among the 42 amino acid residues of the liver-type enzyme that differed from those of the lung-type one were located in the ␣-helix or ␤-sheet, and the other 30 amino acid residues were located in loop structures of the tertiary structure of the liver-type PGF synthase, as inferred from data on human aldose reductase (24,25) and rat 3␣-HSD (26), which showed 46 and 70% identity, respectively, in terms of amino acid sequence with bovine liver-type PGF synthase. As a general rule, an amino acid(s) located in an ␣-helix or a ␤-sheet is involved in supporting the tertiary structure and that in loop structures of aldo-keto reductases is related to define substrate specificity (23,27).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve amino acid residues among the 42 amino acid residues of the liver-type enzyme that differed from those of the lung-type one were located in the ␣-helix or ␤-sheet, and the other 30 amino acid residues were located in loop structures of the tertiary structure of the liver-type PGF synthase, as inferred from data on human aldose reductase (24,25) and rat 3␣-HSD (26), which showed 46 and 70% identity, respectively, in terms of amino acid sequence with bovine liver-type PGF synthase. As a general rule, an amino acid(s) located in an ␣-helix or a ␤-sheet is involved in supporting the tertiary structure and that in loop structures of aldo-keto reductases is related to define substrate specificity (23,27).…”
Section: Discussionmentioning
confidence: 99%
“…They catalyze the 4-pro-R hydride transfer from NADPH to the acceptor carbonyl on the steroid substrate in an ordered bi-bi reaction where NAD(P)(H) binds first and leaves last (16,17). Rat liver 3␣-HSD (AKR1C9), which shares 69% sequence identity with its human homologs, represents the best system to relate structure to function for HSDs, because crystal structures exist for the apoenzyme (E) (18), the E⅐NADP ϩ binary complex (19), and the E⅐NADP ϩ ⅐testosterone ternary complex (where testosterone is a competitive inhibitor) (20). These "snapshots" of the enzyme along the reaction pathway reveal that significant conformational changes occur upon the binding of each ligand and provide a structural basis for the ordered bi-bi mechanism (Fig.…”
mentioning
confidence: 99%
“…2B). The number of interactions is lower than that for AKRs of the first subfamily, such as human ADR holoenzyme and rat 3␣-HSD, both of which have 19 hydrogen bonds, 3 salt bridges, and 1 aromatic stacking (2,4). Fluorescence quenching assay (data not shown) revealed that the K d value of TbPGFS for NADPH (5.3 M) was 1 order of magnitude higher than that of rat 3␣-HSD, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Histidine facilitates proton donation during reduction (46) or orientates the substrate carbonyl in the active site (9,43), whereas lysine helps proton removal by tyrosine during oxidation by making a hydrogen bond that lowers the pK a value of the tyrosine. Aspartate forms a salt bridge to stabilize lysine (3,4,40). In order to catalyze the oxidation/reduction reaction according to this mechanism, tyrosine OH has been involved in hydrogen bond networks with histidine and lysine.…”
Section: Figmentioning
confidence: 99%